MiR-2 contributes to WSSV infection by targeting Caspase 2 in mud crab (Scylla paramamosain). (December 2021) - Gong, Yi; Chen, Jiao; Cui, Yalei; Li, Shengkang
Abstract: Caspase 2 is widely studied for its function in the regulation of apoptosis in mammals. Despite the fundamental role of apoptosis during the anti-viral immune response, the relationship between Caspase 2 and virus infection has not been extensively explored in invertebrates. Also, whether or not miRNAs involve this process remains unclear. To address this issue, the miRNA-mediated regulation of Caspase 2 in mud crab ( Scylla paramamosain ) ( Sp -Caspase 2) was characterized in this study. Sp -Caspase 2 contains an open reading frame (ORF) of 969 bp encoding 322 deduced amino acids and possesses a conserved CASc domain. The results suggested that Sp -Caspase 2 could suppress white spot syndrome virus infection via apoptosis induction. The further data showed that Sp -Caspase 2 was directly targeted by miR-2 in mud crab. Silencing or overexpression of miR-2 could affect apoptosis and WSSV replication through the regulation of Sp -Caspase 2 expression. Taken together, these results demonstrated the crucial role of the miR-2-Caspase 2 pathway in the innate immunity of mud crabs and revealed a novel mechanism in the anti-viral immune response in marine invertebrates. Highlights: Caspase 2 is significantly upregulated during WSSV infection in mud crab. Caspase 2 can suppress WSSV infection via apoptosis induction. Caspase 2 is directly targeted by miR-2 in mud crab. miR-2 can affect apoptosis and WSSV replication through regulating the expression level of Caspase 2.